2007
DOI: 10.1016/j.schres.2007.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide levels in cerebrospinal fluid of first-episode schizophrenic patients: Impact of cannabis use

Abstract: Background: Previous studies have shown that cerebrospinal fluid (CSF) from schizophrenic patients contains significantly higher levels of the endogenous cannabinoid anandamide than does CSF from healthy volunteers. Moreover, CSF anandamide levels correlated inversely with psychotic symptoms, suggesting that anandamide release in the central nervous system (CNS) may serve as an adaptive mechanism countering neurotransmitter abnormalities in acute psychoses. In the present study we examined whether cannabis use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
178
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(192 citation statements)
references
References 42 publications
9
178
2
3
Order By: Relevance
“…Previous studies have found increased levels of endocannabinoids in blood and CSF of patients with schizophrenia (Leweke et al, 1999;De Marchi et al, 2003;Giuffrida et al, 2004;Leweke et al, 2007). A possible mechanism leading to the reduced expression of the CB 1 receptors in socially isolated rats is receptor down-regulation in response to an increase in endocannabinoid levels (e.g., AEA).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have found increased levels of endocannabinoids in blood and CSF of patients with schizophrenia (Leweke et al, 1999;De Marchi et al, 2003;Giuffrida et al, 2004;Leweke et al, 2007). A possible mechanism leading to the reduced expression of the CB 1 receptors in socially isolated rats is receptor down-regulation in response to an increase in endocannabinoid levels (e.g., AEA).…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies have not shown cannabinoid-induced disruption of sensorimotor gating (Stanley-Cary et al, 2002;Bortolato et al, 2005). Also, increases in CB 1 receptor density in frontal cortex subregions have been identified in post-mortem schizophrenic brains (Dean et al, 2001;Zavitsanou et al, 2004), and elevated levels of AEA were detected in cerebrospinal fluid (Leweke et al, 1999;Giuffrida et al, 2004;Leweke et al, 2007) and blood (De Marchi et al, 2003) of anti-psychotic naïve schizophrenics.…”
Section: Introductionmentioning
confidence: 99%
“…The neurobiological mechanisms underlying this increased psychosis susceptibility are poorly understood (D'Souza et al, 2009;Gage et al, 2013). However, some studies have found that frequent cannabis exposure may downregulate AEA signalling in patients with schizophrenia, but not in healthy individuals (Leweke et al, 2007). It has also been described that FEP patients who use cannabis present cognitive impairment associated to altered brain structure in particular areas rich in CB1 (Bangalore et al, 2008;Ho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CSF anandamide levels decrease when people with psychosis are treated with typical antipsychotic medications with high dopaminergic blockade, but not when they are treated with newer atypical agents with proportionally greater serotonergic antagonism [59]. People with schizophrenia and a history of chronic cannabis use do not have elevation in CSF anandamide levels [61], suggesting that cannabis use may suppress the brain's natural ability to temper a psychotic process, and pointing towards a potential biological mechanism underlying the cannabis-psychosis link in vulnerable individuals. In healthy volunteers who regularly use cannabis, CSF anandamide levels are decreased and 2-AG levels are increased compared with infrequent cannabis users [62].…”
Section: The Ecs and Psychosismentioning
confidence: 99%